1992
DOI: 10.1530/jrf.0.0940097
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal inhibition of puberty in domestic gilts is overcome by melatonin administered orally, but not by implant

Abstract: The ability of exogenous melatonin, applied either orally or by implant, to overcome the seasonal inhibition of puberty in domestic gilts was tested in two experiments. In Expt 1, 24 gilts received two melatonin implants at 126 days of age and again at 161 days and 196 days, while 24 gilts acted as controls. All gilts were slaughtered at a mean age of 223 days. Blood samples were collected by venepuncture from eight gilts in each treatment at 126, 144 and 178 days of age and the plasma was assayed for melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The present findings are in accordance with the findings of Paterson et al (1992) who reported that daily feeding of 1 mg melatonin increased the proportion of gilts which reach puberty. Among the 24 gilts which were fed melatonin 15 (56.6%) reached puberty compared with six of the 25 (24%) control gilts.…”
Section: Resultssupporting
confidence: 93%
“…The present findings are in accordance with the findings of Paterson et al (1992) who reported that daily feeding of 1 mg melatonin increased the proportion of gilts which reach puberty. Among the 24 gilts which were fed melatonin 15 (56.6%) reached puberty compared with six of the 25 (24%) control gilts.…”
Section: Resultssupporting
confidence: 93%
“…Secretion of LH in the long-day gilts was not affected by the continuous high concentration of plasma melatonin provided by the implants, suggesting that the inhibition of development of the hypo-pituitary-ovarian axis imposed by the long-day photoperiod was not overcome by the implants. This suggestion is supported by the recent observation of Paterson (1990), that melatonin implants given to gilts under shed conditions in the summer did not prevent the seasonal inhibition of puberty, which is mediated by daylength (Paterson & Pearce, 1990). In sheep (Lincoln & Ebling, 1985;English et al, 1986), deer (Adam et al, 1989) and goats (McGregor et al, 1989), melatonin implants can stimulate reproductive activity under inhibitory photoperiods, but this does not appear to be the case in gilts.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, Andersson et al [1998] showed that, in boars, a short-day lighting regimen advances testicle maturation. It has also been shown that afternoon oral administration of melatonin can override the seasonal delay of the puberty [Diekman et al, 1991;Paterson et al, 1992b].…”
Section: Discussionmentioning
confidence: 99%